Development of a protein nanoparticle platform for targeting EGFR expressing cancer cells. Issue 7 (27th October 2014) - Buecheler, Jakob W.; Howard, Christopher B.; de Bakker, Christopher J.; Goodall, Stephen; Jones, Martina L.; Win, Thinzar; Peng, Tao; Tan, Cher Heng; Chopra, Akhil; Mahler, Stephen M.; Lim, Sierin
Abstract BACKGROUND A range of protein‐based nanoparticles has been developed for cancer drug delivery and diagnostics. This includes the E2 protein derived from the pyruvate dehydrogenase complex in Geobacillus stearothermophilus which assembles into a 60‐subunit protein cage structure that is capable of encapsulating cancer therapeutics. In this study antibody fragments targeting the epidermal growth factor receptor (EGFR) were tethered to the surface of E2 protein nanoparticles to determine whether the protein nanoparticles could be specifically targeted to EGFR overexpressing cancer cells. RESULTS Variants of the anti‐EGFR antibody fragment and the E2 protein containing specific cysteine residues (E2ΔN17A186C) were conjugated using a maleimide‐specific crosslinker. Electron microscopy and dynamic light scattering analysis indicated that the cysteine modified E2 protein correctly assembled into a 25–30 nm particle. The conjugation of the anti‐EGFR antibody fragment (26 kDa) with a subunit of the E2 protein (26 kDa) was confirmed by mass spectrometry with an estimated molecular weight of 52 kDa. The binding of the conjugated E2 particle to native EGFR on MDA MB 231 cells and recombinant EGFR was confirmed using flow cytometry and biolayer interferometry, respectively. CONCLUSIONS In this study, proof‐of‐principle that an EGFR‐targeting scFv can be stably conjugated to the cysteine variant E2ΔN17A186C protein nanoparticle without loss of targeting capability has been demonstrated. Conceptually scFv antibody fragments reactive with other important cancer targets could be utilized and presents the opportunity for generation of multi‐targeted protein nanoparticles by conjugating various scFvs with different specificities on the same particle. © 2014 Society of Chemical Industry